Post-Conflict Recovery : Institutions, Aid, or Luck? - David, Antonio (IMF Working Papers; Working Paper ;, 2011)
This paper identifies the factors linked to cross-country differentials in growth performance in the aftermath of social conflict for 30 sub-Saharan African countries using panel data techniques. Our results show that changes in the terms of trade are the most important correlate of economic performance in post-conflict environments. This variable is typically associated with an increase in the marginal probability of positive economic performance by about 30 percent. Institutional quality emerges as the second most important factor. Foreign aid is shown to have very limited ability to explain differentials in growth performance, and other policy variables such as trade openness are not found to have a statistically significant effect. The results suggest that exogenous factors ("luck") are an important factor in post-conflict recovery. They also highlight the importance in post-conflict settings of policies to mitigate the macroeconomic impact of terms of trade volatility (including countercyclical macroeconomic policies and innovative financing instruments) and of policies to promote export diversification.